About Modern Militarism. How Russian Cinematography Familiarized with Chechen Wars - Kajtoch, Wojciech (Media and Language, 2018)
In the article, the author analyses 19 feature movies and TV series produced from 1996 to 2010 by Russians and dedicated to Chechnya. The main observation is that during that time the approach to this particular subject was changing. The movies made in the years 1996-98, right after the Russian army had lost the so-called First Chechen War, propagated pacifistic ideas or suggested messianic explanation of those events. However, the movies made during the Second Chechen War (1999-2006) were dominated by praise for the Russian soldier as a defender of true Russian national and orthodox traditions. A picture of the enemy changed as well: no longer was it a Chechen, but an international Muslim terrorist. Finally, after 2006, Russian film industry started creating more profound, realistic movies, some of which focused on more universal moral problems.